Top 100 Most Cited Articles on the use of Ozone in Dentistry: Bibliometric Analysis - , Olga Beatriz Lopes Martins; , Marco Túllio Becheleni; , Ricardo Grillo; , Endi Lanza Galvão; , Saulo Gabriel Moreira Falci (Archives of Current Research International, 2024)
Introduction: c density (number of citations per year), first author's country, year of publication, study design and subject. VOSviewer software was used to create graphical bibliometric maps. Results: The total number of citations papers which from 13 to 180, and only eight were cited more than 100 times. Papers were published from 1997 to 2022, mainly in dentistry journals. The studies originated from 30 different countries and the most papers were from Germany (16%) and Turkey (15%). In total, 250 keywords were used and the most used were ozone 50 (20%), dentistry 8 (3,2%) and periodontitis 7 (2,8%). Conclusions: 1) Germany was the main country that contributed to field research on the use of ozone in dentistry 2) The University of Basel was the most productive university in the researched field; 3) Clinical Oral Investigations was the journal that led the ranking with the most articles published, 4) The keyword ozone was the most used in the articles; 5) Oral and maxillofacial surgery was the research area most addressed by the 100 most cited articles.